Crossing the gates of Alaska : one man, two dogs, 600 miles off the map - Metz, Dave (Citadel Press, 2010)
In this true account, the author shares his death-defying three-month journey though the Arctic outback where his six hundred-mile trek took him to the remotest regions of the untamed North--and where his sense of adventure and unwavering spirit led to his survival.